Fluorosis dental en escolares de instituciones educativas privadas. Medellín, Colombia, 2007 (2010)
ABSTRACT: The objective of this study was to establish the prevalence of dental fluorosis among 6-13-year-old children who attended private schools in 2007 in Medellin, Colombia. Methods: seven hundred and fifty two children of 20 private schools selected at random were examined. Two dentists who were trained and calibrated in dental fluorosis diagnosis carried out the clinical evaluation of the children after dental brushing. The labial surfaces of maxillary teeth were examined by visual inspection and with natural light. Thylstrup and Fejerskov index (TFI) for dental fluorosis was used to diagnose and register the alteration. Results: the prevalence of dental fluorosis among school children was 79.1% (TFI ≥ 1); of which 50.8% had only mild degree (TFI1 or 2 ), while 5.1% of the children had severe fluorosis (TFI ≥ 5). Besides, it was found that 17% had TFI ≥ 1 in 50% or less of the teeth. Conclusions: the prevalence of dental fluorosis in children of private schools of Medellin was high, although a mild degree was more prevalent. Formulation of intervention strategies by health authorities are needed in order to contribute to the risk control processes of dental fluorosis.